Analisis Prediksi Kebangkrutan (Financial Distress) Menggunakan Metode Altman Z-Score Dan Springate Pada PT. Indonesia Transport Dan Infrastructure Tbk - Indah Putri Septiana; Ustadus Sholihin; Zulfia Rahmawati (STIKes Ibnu Sina Ajibarang, 2023)
The air transportation business in Indonesia has experienced a rapid increase seen from the number of airlines established in Indonesia. The increasing number of airlines makes the competition increasingly fierce in building a company. So the company can experience financial difficulties that can lead to bankruptcy. One of the airline companies experiencing financial distress is PT. Indonesia Transport and Infrastructure Tbk. This research aims to analyze and predict the bankruptcy of the company PT. Indonesia Transport and Infrastructure Tbk. This research uses the Altman Z-Score and Springate methods. The data collection technique used in the research is secondary data in the form of PT's annual financial report. Indonesia Transport and Infrastructure Tbk for the 2017-2021 period. The results of this research state that in 2017 the company experienced distress with a z-score classification of -2.2920 and Springate -0.5127. In 2018 the company experienced distress with a classification of -2.9939 and Springate -0.4330. In 2019 the company experienced distress with a z-score classification of -4.0886 and Springate -0.5974. In 2020 the company experienced distress with a z-score classification of -6.8293 and Springate -0.7776. In 2021 the company experienced distress with a z-score classification of -8.0491 and Springate -0.5821.